Romania: Public–Private Divide in a Dual-Track System - Mihut, Georgiana (International Higher Education, 2022)
States can ensure that higher education remains a public good by providing free or low-cost high-quality education either to all students or to students who otherwise could not afford it. It is often assumed that public good-oriented provision is offered by state-funded universities. The reality of the public–private-good dichotomy is much messier in many countries, including Romania.